História Indígena no Brasil Independente: Da ameaça do desaparecimento ao protagonismo e cidadania diferenciada - Baniwa, Gersem (2023)
The Brazilian indigenous has Always been a constitutive part of the process of territorial, social and political formation of Brazil and its sociocultural, economic and geopolitical conformation cannot be understood here for thousands of years, with their forms od sociocultural organization and domain territorial. Indigenous peoples contributed with the riches of their lands, with their millenary knowledge and with their sweat and blood to the Brazilian nation. This narrative exercise of indigenous history in Brazil is also one exercise in the autonomy of indigenous thinking, as a subject of its history and destiny, belying the traditional view of its passivity in the face of the process of conquest and construction of Brazil.